Differential Expression of Three Dopamine Receptors in Varroa-Resistant Honey Bees. Issue 1 (23rd January 2022) - Bilodeau, Lelania; Beaman, Lorraine
Abstract: Various stocks of honey bees ( Apis mellifera L. (Hymenoptera: Apidae)) employ multiple mechanisms to control varroa mite ( Varroa destructor Anderson & Trueman (Mesostigmata: Varroidae)) infestations. Identification of trait-associated genes and markers can improve efficiency of selective breeding. Dopamine receptors show promise in this regard in their association with numerous traits in honey bees, high plasticity, and indicated association with varroa resistance through QTL analysis. We assessed the relationship between exposure to mite-infested brood and gene expression of the honey bee dopamine receptors, Amdop 1, Amdop 2, and Amdop 3, in bees and stocks with known levels of varroa resistance, in Spring 2016 (VSH vs Italian) and Summer 2019 (Pol-line vs Italian). Relative mRNA expression levels varied both by honey bee stock and before/after exposure to varroa-infested brood, in 7-, 10-, and 14-day-old bees. However, the trials revealed contrasting patterns in expression of the three dopamine receptors. In 2016, downregulation was evident in VSH bees, but varied by days post-emergence and by gene. The 2019 trial showed upregulation post-exposure in both stocks, and at all ages, for Amdop 1, Amdop 2, and Amdop 3, with the exception of 14 d Italian bees for Amdop 2 and Amdop 3. Stock comparison in 2019 showed upregulation of all three dopamine-like receptors in post-exposure bees of all ages. Season and associated differences in mite loads may have contributed to the differences observed across trials. Differential expression of all three dopamine receptors suggests a role for the dopaminergic system in varroa resistance and suggests that further characterization of these receptors for breeding potential is warranted.